Implications of Leather Tanning Wastewater Exposure for Soil Bacteria Viability and Phosphate Solubilizing Activity - Wijaya Ratih, Yanisworo; Mujahidin, Rohmat; Setyawan, Rizky Putra (KnE Life Sciences, 2022)
Leather tannery wastewater pollutes the environment because it contains BOD, COD, and chromium at levels above safe thresholds. The main objective of this study was to determine the effect of exposure to tannery wastewater on the viability of the soil PSB community and selected PSB isolates, and to examine the ability of selected bacterial isolates to dissolve phosphate in Picovskaya’s broth medium supplemented with tannery wastewater. The viability of the bacterial community was determined based on their growth in soil exposed to the waste at concentrations of 30, 60 and 100%, under field capacity moisture conditions, while the ability of the isolates to dissolve phosphate was observed using liquid Pikovskaya’s medium which was added to the waste so that the concentration reached 30, 60, and 100%. The bacterial isolates RP-1 and RP-2 were used, which were obtained from the soil surrounding the tannery which was contaminated with leather tanning waste. The parameters that were analyzed were the number of cells and the amount of soluble phosphate. The number of cells was determined through the pourplate method using an agar nutrient medium, and the amount of soluble phoshate was examined using the P chlorostannous reduced molybdophosphoric acid blue method. According to the findings of this study, exposure to effluents reduced PSB viability in the soil. Exposure to waste also negatively affected cell viability and the ability of isolates to solubilize phosphate. Keywords: Wastewater, tannery, viability, ability, phosphate, solubilization